SISTEM INFORMASI STOK BARANG MENGGUNAKAN METODE CLUSTERING KMEANS (STUDI KASUS RMD STORE) - Jabbarmuhammad Jabbar (Universitas Majalengka, 2022)
This inventory information system was created to obtain information on goods that were sold in large quantities and those that were not sold (less desirable) in order to reduce the buildup of unsold goods and minimize losses caused by goods that were not in demand, therefore we made an application of the inventory information system using the method clustering KMeans case study RMD Store using PHP Laravel and MySqli.